What we learned from the Nokomisag/Grandmothers: Adapting the 4 Rs for storytelling in Indigenous health research - Rieger, Kendra L.; Horton, Mabel; Cook, Lillian; Copenace, Sherry; Bennett, Marlyn; Phillips-Beck, Wanda; Buss, Mandy; Chudyk, Anna; Hornan, Bobbie; Horrill, Tara; Linton, Janice; McPherson, Kim; et al. (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2025)
The Four R principles (4Rs) of respect, responsibility, relevance, and reciprocity were developed in the field of education by Kirkness and Barnhardt and have guided respectful approaches in research. Our purpose was to adapt the 4Rs for storytelling methods in Indigenous health research and identify associated exemplary research practices. Indigenous team members drew on their traditional Cree and Anishinaabemowin languages to formulate revised 4R definitions tailored to storytelling in health research and our location on Turtle Island, Treaty One territory. We used this adapted 4R framework to identify and analyze patterns of exemplary practices in studies (N=178) using storytelling methods. Our findings can guide respectful storytelling research to meaningfully incorporate Indigenous perspectives for the well-being and benefit of Indigenous communities.